925Ethnic differences and determinants of vitamin D deficiency in the UK Biobank. (2nd September 2021) - Sutherland, Joshua; Zhou, Ang; Leach, Matthew; Hyppönen, Elina
Abstract: Background: While controversy remains regarding optimal vitamin D status, the public health relevance of true vitamin D deficiency is undisputed. There are few contemporary cross-ethnic studies investigating the prevalence and determinants of very low 25-hydroxyvitamin D [25(OH)D] concentrations. Methods: We used data from 440, 581 UK Biobank participants, of which 415, 903 identified as white European, 7, 880 Asian, 7, 602 black African, 1, 383 Chinese, and 6, 473 of mixed ancestry. 25(OH)D concentrations were measured by DiaSorin Liaison XL and deficiency defined as ≤ 25 nmol/L 25(OH)D. Results: The prevalence of 25(OH)D deficiency was highest among participants of Asian ancestry (57.2% in winter/spring and 50.8% in summer/autumn; followed by black African [38.47%/30.78%], mixed ancestry [36.53%/22.48%], Chinese [33.12%/20.68%] and white European [17.45%/5.90%], P < 1.0E-300). Participants with higher socioeconomic deprivation were more likely to have 25(OH)D deficiency compared to less deprived (P < 1.0E-300 for all comparisons), with the pattern being more apparent among those of white European ancestry and in summer (Pinteraction <6.4E-5 for both). In fully-adjusted analyses, regular consumption of oily fish was effective in mitigating ≤25 nmol/L 25(OH)D deficiency across all ethnicities, whilst outdoor-summer time was less effective for black Africans than white Europeans (OR: 0.89; 95% CI: 0.70, 1.12 and OR: 0.40; 95% CI: 0.38, 0.42, respectively). Conclusions: Vitamin D deficiency remains an issue throughout the UK, particularly in lower socioeconomic areas and the UK Asian population, half of whom have vitamin D deficiency across seasons. Key messages: The prevalence of 25(OH)D deficiency in the UK is alarming, with certain ethnic and socioeconomic groups considered particularly vulnerable.